Determinants of COVID-19 vaccine uptake among Nigerians: evidence from a cross-sectional national survey - Temitope Olumuyiwa Ojo; Ayodeji Oluwole Ojo; Olajumoke Elizabeth Ojo; Bosede Olufunmilayo Akinwalere; Adebowale Femi Akinwumi (BMC, 2023)
Abstract Background COVID-19 ranks as one of the largest public health threats in recent times. It is associated with huge health, economic and social consequences. Although vaccination is an effective control measure, COVID-19 vaccine uptake has been suboptimal in many low/middle income countries. Hence this study assessed the factors influencing COVID-19 vaccine uptake among Nigerian households. Data and methods This study analyzed secondary data from the COVID-19 High-Frequency Phone Survey of Households that was collected by the National Bureau of Statistics between November 2021 and January 2022. Relevant data were analyzed using descriptive statistical tools and the Multivariate Regression model. Results Out of 2370 respondents, only 32.8% of the respondents were vaccinated against COVID-19. Respondents living in urban areas (34.4%) had a higher level of COVID-19 vaccine uptake relative to those living in rural Nigeria (30.9%). Results from the Multivariate Regression model revealed that adults aged ≥ 60 years (OR 2.20; p = 0.012), respondents with primary (OR 1.72; p = 0.032), secondary (OR 1.77; p = 0.025) and tertiary education (OR 3.03; p < 0.001), respondents with access to health insurance (OR 1.68; p = 0.004), those who obtained vaccine information from health workers (OR 3.92; p < 0.001), the government (OR 3.22; p < 0.001), and the mass media (OR 1.75; p = 0.003) were more likely to be vaccinated. Also, respondents living in North Central (OR 2.02; p < 0.001), North East (OR 1.48; p = 0.039), South West (OR 2.63; p < 0.001), and South South (OR 1.49; p = 0.031) regions had higher odds of being vaccinated. Conclusions The study recommends increased media campaigns and advocacy for COVID-19 vaccination in the South East and North West regions. Persons with no formal education and younger persons aged 18-29 years should be targeted with COVID-19 vaccine-related information given that they were less likely to be vaccinated. Dissemination of relevant information through government sources, mass media and health workers is encouraged so as to positively influence decisions to receive COVID-19 vaccines among citizens.